The Inner Harbour - Background Document on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour – Policy Recommendations on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

Design Thinking associated with R&D: Process Management and Knowledge Transfer for the Creative Industries - Cerejo, Joana; Barbosa, Álvaro (LAP LAMBERT Academic Publishing, 2014)
The difficult task of innovation is a key facet of Research & Development (R&D) institutions. To Design, innovation is to make the project technically feasible, economically viable, merchandising interesting and emotionally engaging. Design Thinking integrated with R&D organizations can foster the relationship between Universities and new markets. By addressing these topics, this book researches new emerging design methods and provide an overview of Design Thinking tools that can be applied in an early stage of the R&D research process to produce meaningful results. It is taken into account that design, through Design Thinking, extends to the experience that costumers/users have with products/services or even multidimensional experiences, which is a relevant input for R&D innovation development. In fact, the establishment of coherent guidelines for the Design Thinking process is a very complex task, due to its interdisciplinary requirements, that convey many diverse mindsets. The main focus of this book is creating an analysis toolkit that enables non-specialist and specialist users to perform high-quality design solutions.